Case Report: Coadministration of TNF-α blockade as an effective adjunctive strategy in the treatment of ANCA-negative EGPA with refractory peripheral neuropathy - Tang, Dabin; Jiang, Yubao; Yang, Shuo; Wei, Jiaxin; Xie, Jingjing; Zhang, Jianyong (Frontiers in Pharmacology, 2025)
Eosinophilic granulomatosis with polyangiitis (EGPA) is characterized by abnormal eosinophilia and extravascular eosinophilic granuloma formation. Conventional treatments combining glucocorticoids and immunosuppressants can alleviate the condition in most patients with EGPA. However, the efficacy of blocking tumor necrosis factor (TNF)-α-mediated inflammatory reactions in managing EGPA remains controversial. Here, we report a case of refractory EGPA that did not respond to glucocorticoid pulse therapy and adequate cyclophosphamide. The disease was ultimately controlled through the coadministration of etanercept.